Pengaruh Pendapatan Asli Daerah Terhadap Alokasi Belanja Modal Dengan Budget Ratcheting Sebagai Variabel Moderating - Aisyah Nur Hidayah; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2022)
The place of research is in the office of the Regency/City Government of West Sumatra Province. The research sample is LKPD time series data in the form of district and city APBD and LRA in West Sumatra Province from 2016-2019. The approach uses moderated regression analysis (MRA). The study concluded that the ratcheting effect occurred on the PAD budget. Ratcheting effect occurs in capital expenditures, PAD does not affect Regional Expenditures. Budget ratcheting weakens the relationship between Regional Original Revenue and Regional Expenditure.